2000
DOI: 10.1111/j.0014-3820.2000.tb00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Character Displacement in Polyphenic Tadpoles

Abstract: Biologists have long known that closely related species are often phenotypically different where they occur together, but are indistinguishable where they occur alone. The causes of such character displacement are controversial, however. We used polyphenic spadefoot toad tadpoles (Spea bombifrons and S. multiplicata) to test the hypothesis that character displacement evolves to minimize competition for food. We also sought to evaluate the role of phenotypic plasticity in the mediation of competitive interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
182
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(185 citation statements)
references
References 37 publications
2
182
0
Order By: Relevance
“…1). Several studies recently have reported different reaction norms in populations occupying habitats with different levels of selection (Pfennig & Murphy, 2000;Laurila et al, 2002;Trussell & Nicklin, 2002). Different plastic responses, or different reaction norms between populations, provide good evidence that those different responses are adaptive (Laurila et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Several studies recently have reported different reaction norms in populations occupying habitats with different levels of selection (Pfennig & Murphy, 2000;Laurila et al, 2002;Trussell & Nicklin, 2002). Different plastic responses, or different reaction norms between populations, provide good evidence that those different responses are adaptive (Laurila et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A positive relationship between plasticity in the frequency of the broad headed morph and egg size would provide necessary evidence for adaptive integration of plasticity and egg size and support the idea of coadaptation (Doughty 2002). However, natural selection can act on morphological plasticity and trophic polyphenism (Moran 1992), driving evolution of different reaction norms among populations (Pfennig & Murphy, 2000;Laurila et al, 2002;Trussell & Nicklin, 2002). Plasticity in the frequency of the broad-headed morph among natural populations may be caused by the adaptive response of the plasticity itself, which would support the idea that plasticity and egg size are optimized independently.…”
Section: Introductionmentioning
confidence: 86%
“…However, intensive studies of young species in other groups of organisms including Anolis lizards on Caribbean islands (Losos 2009), spadefoot toad tadpoles in the American southwest (Pfennig and Murphy 2000), and Darwin's finches on Galápagos islands (Grant and Grant 2006), have uncovered similar mechanisms, suggesting that they occur widely (though not necessarily universally). Competition and coevolution are likely to be major drivers of species differentiation in nature.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, evaluating the role of competition and coevolution in the evolution of diversity must go beyond pattern to illuminate the mechanisms driving divergence. Intensive recent research on a few systems, including Darwin's finches (Grant and Grant 2006), spadefoot toads (Pfennig and Murphy 2000), Caribbean island lizards (Losos 2009) and threespine stickleback (Schluter and McPhail 1992;Schluter 2003) have helped to build a more comprehensive picture of the role of competition and coevolution. In this article, I give an overview of progress from studies of one of these groups, the threespine stickleback of small coastal lakes in British Columbia, Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Tadpoles were not fed natural live food (e.g., fairy shrimp), because doing so can induce the production of carnivore-morph tadpoles, which potentially cannibalize other tadpoles (reviewed in Pfennig and Murphy 2000). Live food can enhance development times of spadefoots (Simovich 1985;Simovich et al 1991), however, so our measures of development times on fish food are potentially conservative (see Discussion for comparison of our results to other studies).…”
Section: Experimental Crossesmentioning
confidence: 90%